Train Traffic as a Powerful Noise Source for Monitoring Active Faults With Seismic Interferometry - F. Brenguier; P. Boué; Y. Ben‐Zion; F. Vernon; C.W. Johnson; A. Mordret; O. Coutant; P.‐E. Share; E. Beaucé; D. Hollis; T. Lecocq (Geophysical Research Letters)
Abstract Laboratory experiments report that detectable seismic velocity changes should occur in the vicinity of fault zones prior to earthquakes. However, operating permanent active seismic sources to monitor natural faults at seismogenic depth is found to be nearly impossible to achieve. We show that seismic noise generated by vehicle traffic, and especially heavy freight trains, can be turned into a powerful repetitive seismic source to continuously probe the Earth's crust at a few kilometers depth. Results of an exploratory seismic experiment in Southern California demonstrate that correlations of train‐generated seismic signals allow daily reconstruction of direct P body waves probing the San Jacinto Fault down to 4‐km depth. This new approach may facilitate monitoring most of the San Andreas Fault system using the railway and highway network of California.